Respon Pertumbuhan Bibit Kelapa Sawit di Pre Nursery terhadap Macam dan Interval Waktu Pemberian Urin - Fajar Khoerudin; Wiwin Dyah Ully Parwati; Achmad Himawan (AGROISTA : Jurnal Agroteknologi, 2023)
This study aims to determine the growth response of oil palm seedlings in the pre nursery to the type and time interval of urine aplication. The research was conducted at Kebun Pendidikan dan Penelitian Institut Pertanian Stiper Yogyakarta, Maguwoharjo, Depok, Sleman, Yogyakarta Special Region. This research was conducted from November 2022 to January 2023. The study used a factorial experimental design and a completely randomized design (CRD) consisting of two factors. The first factor which consist of four levels namely control (NPK, N), cow urine, goat urine and rabbit urine.Â  The second factor which consist of three levels namely once every three days, once every five days and once every seven days. There were twelve treatment combinations and repeated five times so that there were sixty plant samples. Using ANOVA (Analysis of Variance) with a significance level of five percent this data was analyzed. Futher test using DMRT (Duncan Multiple Range Test) with a significance level of five percent if there is a significant difference. There was an interaction between the type dan time interval of urine aplication on shoot fresh weight and shoot dry weight. Control (NPK, N) and type of urine had the same effect, meaning that livestock urin could replace chemical fertilizers (NPK, N). The time inteval for giving urine once every seven days was the best compared to once every three days and once every five days.